2020
DOI: 10.1038/s41598-020-62433-w
|View full text |Cite
|
Sign up to set email alerts
|

HgCdTe mid-Infrared photo response enhanced by monolithically integrated meta-lenses

Abstract: for S m = 5 μm × 5 μm or S m = 10 μm × 10 μm. Further, the meta-lens exhibits a good dispersion tolerance over the wavelength range from 3.3 μm to 5 μm. The averaged detectivity enhancement over this spectrum range is around 3 times for S m = 5 μm × 5 μm and 2 times for S m = 10 μm × 10 μm. The angular response of the meta-lens integrated detector depends on the focal length. For a focal length of 73 μm, the AOV for a 5 μm × 5 μm photosensitive area is 4.0°. When the focal length is reduced to 38 μm, the AOV f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…For a meta-lens with diameter of 200 µm, the diameter of the focused region is around 10-20 µm, depending on the NA (Figure 3b). Overall, the enhancement ratio of light intensity in the focused region is ~20, which is similar to previously reported experimental values [26].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For a meta-lens with diameter of 200 µm, the diameter of the focused region is around 10-20 µm, depending on the NA (Figure 3b). Overall, the enhancement ratio of light intensity in the focused region is ~20, which is similar to previously reported experimental values [26].…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the employment of meta-lenses as optical concentrators could improve the detectivity by a factor of 32. Previous experimental studies of HgCdTe with meta-lenses reported an enhancement ratio of ~5.5, demonstrating that the concept of integration of meta-lenses with infrared detectors should work [26]. The current study mainly focuses on simulation and theoretical calculation, and experimental tests would be conducted to verify such an enhancement factor in the future.…”
Section: Resultsmentioning
confidence: 92%
“…Graphene/HgCdTe heterostructure infrared photodetectors shows responsivity of 2.60 A W −1 working upto mid-infrared wavelength region of 5.2 μm [151]. The state-of-the-art research in HgCdTe alloys has shown enhancement in MIR photoresponse as well as detectivity by integrating monolithically with meta lenses [152]. Ge/perovskite heterostructure photodetector, operating at 1550 nm shows responsivity of 1.4 A W −1 at a low bias of 1 V. The perovskite coating gives the lowest reflection at 1550 nm wavelength and along with type 1 band alignment, aids charge transport from perovskite to Ge [153].…”
Section: Photodetector Performance Of 2d Materials and Hybridsmentioning
confidence: 99%
“…Ndao et al [128] achieved polarization-insensitive, ultrawideband achromatic focusing at visible-near infrared wavelengths by numerical optimization algorithms, and the focusing efficiency exceeded 70%. Li et al [155] reported on monolithically integrating a dielectric polarization-independent metalens into a HgCdTe infrared photodetector, as shown in Figure 7q. The metalens can enormously improve the absorptance, meanwhile reducing the photosensitive area and enhancing the detectivity.…”
Section: Broadband Response Metalenses Integrated Detectionmentioning
confidence: 99%